2008
DOI: 10.1597/07-048.1
|View full text |Cite
|
Sign up to set email alerts
|

The Continuing Multidisciplinary Needs of Adult Patients with Cleft Lip and/or Palate

Abstract: For some patients who have had a cleft lip and/or palate, problems continue into adulthood or arise later in life. These problems are often multiple and treatment often requires the input of more than one specialist. The results of this audit support the need for coordinated multidisciplinary care for adults who have had a cleft lip and/or palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…There is a need for multidisciplinary care for these patients during many stages of their lives 911 . This study is typical of complete cleft care, involving multidisciplinary treatment and analyses of their treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for multidisciplinary care for these patients during many stages of their lives 911 . This study is typical of complete cleft care, involving multidisciplinary treatment and analyses of their treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients request secondary surgical treatment, and several studies have indicated that the greatest concern for the patient is correction of appearance and function of the nose. 15 Earlier studies on nasal airway function among patients treated for UCLP indicate that objectively measured nasal function is extensively impaired; the patients have lower values regarding nasal volume, higher resistance to breathing, and lower results regarding olfaction compared with controls. 6,7 …”
mentioning
confidence: 99%
“…Secondly, our findings will help advocate for greater involvement of psychological professionals in the preoperative and postoperative treatment of patients in order to help maximize positive surgical outcomes. 14,15 The development of an identity devoid of self-confidence and independence occurred over many years and requires much more than surgical correction to be reversed; therefore, psychological intervention may be greatly beneficial.…”
Section: Discussionmentioning
confidence: 99%